CHARACTERIZATION OF SOIL THERMAL PROPERTIES FOR DESIGN OF UNDERGROUND CABLE ROUTES AT THE WIND FARM POWER PLANT AREA, PANYIPATAN AND PELAIHARI SUB-DISTRICT, SOUTH KALIMANTAN - Syamsurijal Rasimeng (JURNAL GEOCELEBES, 2020)
The estimation of soil thermal resistivity is essential for many types of big engineering projects because of the required knowledge about subsurface transmission of either heated fluids or high power currents. Thermal conductivity measurements were carried out at 12 locations, eight measurement point locations in South Kalimantan, the Sapu Angin hill region, sub-district Penyipatan and four points in the area of Kampung Baru, sub-district Pelaihari made at 2-3 variations in depth of 50 to 100 cm, which adjusted to the ability of the soil drilling support equipment to make holes in the soil. Samples were also collected from the locations for physical parameters description that influences thermal resistivity, subjected to grain size distribution and compaction analysis. The calculation of thermal conductivity is done by using CT-Lab software ver. 1.0.2 with a sensor resistance value of 82.69 ohms / m, heater voltage 4.0 V, and heater power 4.3857 W/m. The results show that the thermal conductivity values range from 0.593 to 3.239 W/mK. For the Sapu Angin hill region, sub-district Penyipatan, soil layers are generally in the form of sandy-clay (λ> 1.2 W/mK), but at some points, the value of thermal conductivity in these layers have decreased (λ <1.2 W/mK) due to rainwater infiltration (BH-02, BH-03, BH-04, BH-05, and BH-07). The infiltration causes weakening or loosening of bonds between the constituent particles of the soil. While in the area of Kampung Baru sub-district Pelaihari, the soil layer is generally in the form of sandy-clay, which has not well compacted (BH-08, BH-10, BH-12) with high water content (BH-09).